Relationship between Motivation and Caring Behavior in Indonesian Nurses - Judha, Mohamad (Babali Nursing Research, 2025)
Introduction: The number of nurses has increased from year to year. Since 2016, there have been 300,000 nurses, which continues to grow. This large number has not had an impact on Health Development. A survey in five major cities in Indonesia stated that some nurses do things that are considered unsympathetic. Therefore, this study analyzed the relationship between motivation and caring behavior.Methods: Researchers used a quantitative research method by analyzing the relationship between 2 variables. A sample of 400 nurses from 5 cities in Indonesia, representing several nursing competencies, were asked to answer a validated questionnaire. This study has received ethical approval number SPUP_2023_0026_SR_MJ.Results: Some situations, such as things that cause motivation to care, motivation to behave in caring for patients, show significant results with a p value <0.005. Several factors can increase caring attitudes towards patients, but there are also obstacles in showing quality caring behavior caused by caring attitudes and empathy towards patients.Conclusion: Every professional behavior is always accompanied by motivation, meaning that providing work motivation to subordinates is necessary so that they are willing to work seriously to achieve organizational goals. For that, every nurse who works uses something that can encourage motivation.